Perencanaan Struktur Perkerasan Lentur Jalan Dengan Metode MDPJ 2017 Pada Ruas Jalan Baumata – Penfui Kecamatan Taebenu Kabupaten Kupang: Road Flexible Pavement Structure Planning With 2017 MDPJ Method On The Baumata - Penfui District Road Taebenu, Kupang Regency - Anie A. Tuati; Deasi D. A. A. Daud; Zulfiani A.R. (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Road pavement is a layer of pavement structure that is located on the subgrade. In determining the thickness of flexible pavement in this research, the 2017 Road Pavement Design Manual method was used. The location of this research is the Baumata - Penfui road section in West Baumata Village, Taebenu District, Kupang Regency with a total road length of 3.5 km and a width of 4.5 m. Existing road pavement in the form of macadam along 2.7 km. The data used in this research are primary data in the form of traffic volume, dynamic cone penetrometer and road geometry, while secondary data is in the form of location maps. Based on the results, it was found that the LHR for commercial vehicles was 110 vehicles per day, for the CESA4 value it was 1221707.63 ESAL, for CESA5 it was 1467536 ESAL, for the land CBR value it was 11%. Using the MKJI 2017 method with a design age of 20 years, the pavement structure was obtained, namely LFB class B 12.5 cm, LFA class A 25 cm, HRS-Base 3.5 cm, HRS-WC 3 cm